International economic institutions - Richards, John Hamish (London : New York : Holt, Rinehart and Winston, 1970)
The books is an elementary guide to students with specialty in international development economics. It provides an insight into the fundamental economics problems in 1970.
Bibliography: p. [310]-318.
asm; 14/02/19
Loans
Keywords: International agencies; Developing countries